2021
DOI: 10.30574/wjarr.2021.12.3.0675
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of labor outcome by measuring the angle of progression using two dimensional trans-perineal Ultrasound: A prospective cohort study

Abstract: Background: Failure of descent due to fetal malposition is one of the most common indications for performing surgical deliveries. It has recently been suggested that trans-perineal intra-partum ultrasonography may be useful in assessing fetal head engagement, position and station as well as it’s reliable, cheap, painless and effective tool. Measuring the ‘angle of progression’ could assist in the obstetrician’s decision regarding mode of delivery. Objectives: The primary outcome is to use the AOP to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Angle of progression was significantly higher in spontaneous vaginal delivery group (with cutoff 123° ± 8.5°) as compared with women delivered by vacuum or by CS (113° ± 10.5°) (p = 0.003). 30 In India, a study conducted in 2021 on 200 subjects where AOP was determined by transperineal USG concluded that the probability of CS was nil at an angle ≥116° during the first stage of labor. The cutoff value of AOP for predicting vaginal delivery was 99.6° as determined by ROC.…”
Section: Descent Of Head and Station Of Headmentioning
confidence: 99%
“…Angle of progression was significantly higher in spontaneous vaginal delivery group (with cutoff 123° ± 8.5°) as compared with women delivered by vacuum or by CS (113° ± 10.5°) (p = 0.003). 30 In India, a study conducted in 2021 on 200 subjects where AOP was determined by transperineal USG concluded that the probability of CS was nil at an angle ≥116° during the first stage of labor. The cutoff value of AOP for predicting vaginal delivery was 99.6° as determined by ROC.…”
Section: Descent Of Head and Station Of Headmentioning
confidence: 99%